2012
DOI: 10.1371/journal.pone.0045297
|View full text |Cite
|
Sign up to set email alerts
|

Cell Visco-Elasticity Measured with AFM and Optical Trapping at Sub-Micrometer Deformations

Abstract: The measurement of the elastic properties of cells is widely used as an indicator for cellular changes during differentiation, upon drug treatment, or resulting from the interaction with the supporting matrix. Elasticity is routinely quantified by indenting the cell with a probe of an AFM while applying nano-Newton forces. Because the resulting deformations are in the micrometer range, the measurements will be affected by the finite thickness of the cell, viscous effects and even cell damage induced by the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
163
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 41 publications
17
163
0
Order By: Relevance
“…Therefore, the graph of the Figure 4(b) fits well with the Equation (15). It may be noted that there is no difference between the conventional diagram and rational diagram (Figure 4(a)) in the elastic range since the deformation is low.…”
Section: Resultssupporting
confidence: 65%
“…Therefore, the graph of the Figure 4(b) fits well with the Equation (15). It may be noted that there is no difference between the conventional diagram and rational diagram (Figure 4(a)) in the elastic range since the deformation is low.…”
Section: Resultssupporting
confidence: 65%
“…interpret MA experimental data [3,14]. However, such material models fail to consider the underlying biomechanisms of cell response to mechanical stimuli and a number of studies have demonstrated that passive material model parameters must be artificially altered if any experimental parameter is altered [15,16], i.e.…”
Section: Previous Studies Have Assumed Simple Viscoelastic Constitutimentioning
confidence: 99%
“…The force-indentation (F-Id) curve is then used to determine the elastic moduli, using the Hertz model [26] :…”
Section: Experimental Approach and Data Analysismentioning
confidence: 99%
“…This highlights the fact that the cells are sensitive to the applied forces and the loading rates (measured in N/s) [24] because of their viscoelastic, inhomogeneous and anisotropic nature. Therefore, for characterization of different cell lines it is important to complement AFM vertical indentation measurements by OT measurements following the same scheme [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation